Studi Perbandingan Kuat Tekan Beton Dengan Campuran Limbah Marmer Sebagai Subtitusi Agregat Kasar - Sudarmono, Enjellytha; Mustakim; Kasmaida (Universitas Nusa Putra, 2025)
The waste problem in Indonesia is an unresolved problem. The ever-increasing population increases the amount of waste originating from human activities, both organic and inorganic waste. Like marble waste which is difficult to destroy naturally, research is needed on the use of marble waste into environmentally friendly concrete. The aim of the research is to find out how much the compressive strength of concrete is. This research uses experimental data collection techniques or methods (testing/observation. The research was carried out with the aim that the results of replacing some of the coarse aggregate with marble fragment waste in terms of the compressive strength value of the concrete could be known. The research was designed with variations in replacing marble fragments by 50% in cylindrical concrete with dimensions of 15 cm as the diameter and 30 cm as the height, and the concrete had been aged for 7 days, 14 days and 28 days and its compressive strength would be tested. The highest compressive strength was found in the marble mixture variation of 0.5-1 cm with a concrete age of 28 days, namely 26.86.